2021
DOI: 10.3390/foods10061344
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Phytochemical Traits of Apricots (Prunus Armeniaca L.) for Application in Nutraceutical and Health Industry

Abstract: Apricot (Prunus armeniaca L.) is a nutritious fruit, rich in bioactive compounds, known for their health benefits. The present study attempts to evaluate nutritional (sugars, organic acids, minerals) and nutraceutical traits (total phenolics, flavonoids, carotenoids, antioxidant activity) of six commercial apricot genotypes grown in India. Antioxidant activity was determined using three in-vitro assays, namely CUPRAC (cupric reducing antioxidant capacity), FRAP (ferric reducing antioxidant power) and DPPH (1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Wild apricot fruits dominantly included citric acid between 923-1268 mg/100 g, followed by malic acid (380-567 mg/100 g), ascorbic acid (18.4-23.6 mg/100 g), and tartaric acid (3.1-6.8 mg/100 g) (Table 2). Previously, Alajil et al [50] revealed that citric acid was dominant in apricot fruits and comprised 55% of the organic acids in apricot fruits and ranged from 550 to 1170 mg/100 g, followed by malic acid, which comprised approximately 25% of the organic acids and ranged from 400 to 1430 mg/100 g; these results indicate similarities with this study. In another study, Fan et al [49] presented that malic acid was mainly responsible for sourness of apricots, although malic acid was not the prominent organic acid in all apricot cultivars.…”
Section: Organic Acidssupporting
confidence: 87%
See 3 more Smart Citations
“…Wild apricot fruits dominantly included citric acid between 923-1268 mg/100 g, followed by malic acid (380-567 mg/100 g), ascorbic acid (18.4-23.6 mg/100 g), and tartaric acid (3.1-6.8 mg/100 g) (Table 2). Previously, Alajil et al [50] revealed that citric acid was dominant in apricot fruits and comprised 55% of the organic acids in apricot fruits and ranged from 550 to 1170 mg/100 g, followed by malic acid, which comprised approximately 25% of the organic acids and ranged from 400 to 1430 mg/100 g; these results indicate similarities with this study. In another study, Fan et al [49] presented that malic acid was mainly responsible for sourness of apricots, although malic acid was not the prominent organic acid in all apricot cultivars.…”
Section: Organic Acidssupporting
confidence: 87%
“…Karatas and Sengul [49] found L*, a*, and b* values of 13 main apricot cultivars grown in Turkey between 48.66-64.70; 8.12-19.41 and 18.06-42.45, respectively. In India L*, a*, and b* values of six international apricot cultivars were between 52.10-71.51; 1.03-39.85; and 40.56-62.94, respectively [50]. These results reveal that growing conditions and genetic background strongly affect peel color coordinates of apricots.…”
Section: Morphological Featuresmentioning
confidence: 75%
See 2 more Smart Citations
“…Apricot contains several secondary metabolites [ 11 , 12 , 13 ], many of them being active as antioxidants [ 14 ]. Polyphenols and carotenoids (mainly β-carotene) represent the most abundant classes of phytochemicals contained in this fruit [ 15 ]; such molecules are not only crucial for the antioxidant activity but play a primary role also in the color and taste in fruit [ 4 ].…”
Section: Introductionmentioning
confidence: 99%